Menjaga Kearifan Lokal Dalam Era Globalisasi - Linda Ramisah; Nadila Ramadana; Luthfi Aulia; Eka Darliana; Anisa Noverita (Jurnal Berbasis Sosial, 2026)
Local wisdom serves as the primary foundation of national identity, currently facing significant challenges amidst the rapid flow of globalization. This research aims to examine the importance of preserving local traditional values as a survival strategy in an increasingly anonymous and uniform modern era. Employing a qualitative approach with a literature study method, data were gathered from various scientific literatures, books, and relevant documents, which were then analyzed descriptively. The results indicate that local wisdom functions as a moral "anchor" and a cultural immune system capable of filtering external influences and strengthening social cohesion through values such as mutual cooperation (gotong royong) and deliberation (musyawarah). However, real challenges were identified, including a shift in social interaction due to technological dominance and a sense of cultural inferiority. This study concludes that cultural preservation must not be rigid; rather, it should be achieved through the integration of local values in education (ethnopedagogy) and tradition rebranding strategies within the creative economy sector. Through synergy between education, families, and society, the younger generation is expected to grow into global citizens who remain firmly rooted in Indonesian cultural heritage without being left behind by modern progress.